B.Y.O.C (1,342 Times and Counting). - KAMP, POUL-HENNING (Communications of the ACM, 2011)
The article discusses the advantages of reusing software code for commonly needed algorithms in the field of computer programming. It refers to the principle of Occam's razor, noting that a few algorithms held in an easily accessible code library are preferable to a plethora of distinct algorithms which all do the same thing. Although copyright issues and the multiplicity of programming languages ensure a certain degree of multiplicity, it is noted that this may be optimal, as it provides competition and incentive for further improvement. An example involving cryptographic algorithms is provided.